2016
DOI: 10.3390/polym8080315
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Buckyball: A High-Symmetry Complete Polyhedral Oligomeric Silsesquioxane (POSS)

Abstract: Abstract:In this study, we report UV-MALDI-TOF MS evidence of a fullerene-like silsesquioxane, a high-symmetry polyhedral oligomeric silsesquioxane (POSS or SSO) formulated as R 60 -Si 60 O 90 or T 60 (T = RSiO 1.5 ). The T 60 preparation can be performed using a normal hydrolytic condensation of [(3-methacryloxy)propyl]trimethoxysilane (MPMS) as an example. Theoretically, four 3sp 3 hybrid orbitals (each containing an unpaired electron) of a Si atom are generated before the bond formation. Then it bonds to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A functional organic/inorganic hybrid material has attracted widespread interest. The synergistic combination of organic polymers and inorganic silica has received considerable attention because of the potential for the development of new materials with designed properties by molecularlevel structural manipulation [36][37][38][39][40][41][42] , specifically, polyhedral oligomeric silsesquioxane (POSS)-based hybrid polymers have emerged as unique materials for various applications. The empirical formula of POSS nanostructure is RSiO 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…A functional organic/inorganic hybrid material has attracted widespread interest. The synergistic combination of organic polymers and inorganic silica has received considerable attention because of the potential for the development of new materials with designed properties by molecularlevel structural manipulation [36][37][38][39][40][41][42] , specifically, polyhedral oligomeric silsesquioxane (POSS)-based hybrid polymers have emerged as unique materials for various applications. The empirical formula of POSS nanostructure is RSiO 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has strong attention due its unique physico-chemical properties and reactive organic terminal functional substituents [ 4 , 5 , 6 , 7 , 8 ]. The three-dimensional structure of the silicon–oxygen (Si–O) core is inevitably responsible for high thermal stability and stiffness, whereas the terminal organic reactive functional groups can be enabled to make the covalent bond between POSSs and polymers, which results in the solid progress of organic–inorganic hybrid materials [ 9 , 10 ]. POSS properties have been tuned [ 11 , 12 , 13 , 14 , 15 ] by incorporating various end-group moieties (functionalities), such as acrylates, methacrylate, alcohols, amines, carboxylic acids, epoxides, fluoroalkyls, halides, and imides, through self-polymerization reactions, which include self-condensing vinyl polymerization, poly-condensation reactions, ring-opening polymerization, and “ene-click” reactions [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR, and 28 Si NMR were taken on a Bruker AV 600 NMR spectrometer (600 M) that operated in Fourier transform mode, utilizing tetramethylsilane as an internal reference. using deuterated acetone ((CD 3 ) 2 CO), deuterated chloroform (CD2Cl 3 ), or deuterated dichloromethane (CD 2 Cl 2 ) as solvent.…”
Section: Nuclear Magnetic Resonance Spectroscopy (Nmr)mentioning
confidence: 99%
“…19 Ali Akbari 27 et al designed and synthesized incompletely condensed silsesquioxane with three allyl groups (TAP-POSS), which has both phenyl groups and allyl groups. Zixuan Lei 28 et al used POSS only containing epoxy group in PR and found that after modification, the char yield of the resin at 800 C increased by 26.9%, the crosslinking density of the resin increased by 31.62%, and the mechanical properties were also improved. He also found that when EPOSS was added too much, the PR's crosslinking network was broken, resulting in poor thermal stability and mechanical deterioration.…”
mentioning
confidence: 99%
See 1 more Smart Citation